Obesity and visceral fat: Indicators for anemia among household women visiting a health camp on world obesity day - Ravishekar N Hiremath; Mukesh Kumar; Raghavendra Huchchannavar; Sandhya Ghodke (Elsevier, 2023)
Background: Obesity and anemia are among most common non-communicable diseases not only in India but around the world. These conditions are observed together more among females. Obesity being a risk factor for various lifestyle disease, is hypothesized to affect iron absorption and hence level of hemoglobin. Objectives: To find the prevalence of obesity and anemia among given sample population and to find out various factors affecting obesity and anemia. Methods: A cross sectional study was done among married females visiting a health camp on World Obesity Day. They were assessed using a self-administered semi-structured questionnaire and anthropometric examination. Basic clinical examination, body fat analysis and blood indices were also done. Results: The mean age of study participants was found to be 30.27 ± 5.3 years. 487 (70.78%) of the study participants were found obese with BMI >23 kg/m2 and 61 (8.86%%) participants were found to be anemic. Increasing age, education level, menstrual flow, gravida, parity were found to be significantly associated with obesity. Among participants who were anemic, majority (86.9%) had low visceral fat, suggesting the relationship of anemia and fat metabolism is more related to peripheral fat deposition and not much to visceral fat (p < 0.05). Conclusion: Our study findings suggest there is a need to carry out in-depth longitudinal and multicentric studies on larger population to see the exact relationship between visceral fat/obesity and anemia as in our study, the prevalence of anemia was very less and thus giving confusing results about visceral and total body fat relation with anaemia.